2014
DOI: 10.1016/j.virol.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant myxoma virus lacking all poxvirus ankyrin-repeat proteins stimulates multiple cellular anti-viral pathways and exhibits a severe decrease in virulence

Abstract: Although the production of single gene knockout viruses is a useful strategy to study viral gene functions, the redundancy of many host interactive genes within a complex viral genome can obscure their collective functions. In this study, a rabbit-specific poxvirus, myxoma virus (MYXV), was genetically altered to disrupt multiple members of the poxviral ankyrin-repeat (ANK-R) protein superfamily, M-T5, M148, M149 and M150. A particularly robust activation of the NF-κB pathway was observed in A549 cells followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The advantage for maintenance of multiple yet subtly different ANK/F-box genes within poxviral genomes is not yet known, however several studies have illustrated the importance of the complete set of ankyrin proteins to a successful infection. This has been shown with myxoma virus where in vivo studies showed increased viral attenuation with knockout of ANK repeat protein M-T5 in comparison to knockouts of the ANK/F-box proteins M148R, M149R, and M150R, [ 84 , 95 , 101 ] reflecting a more potent role for M-T5 in enabling a virulent and systemic infection. A prominent role in virulence and host-range for the ANK repeat proteins is also shown by the characterisation of attenuated strains generated by extensive cell-passage, which frequently and apparently preferentially, result in deletion or mutation of ANK repeat proteins, as shown with attenuated strains of myxoma virus, sheeppox virus, fowlpox virus, and orf virus [ 33 , 101 , 102 , 103 ].…”
Section: Poxviral Ank/f-box Protein Phylogeneticsmentioning
confidence: 84%
See 1 more Smart Citation
“…The advantage for maintenance of multiple yet subtly different ANK/F-box genes within poxviral genomes is not yet known, however several studies have illustrated the importance of the complete set of ankyrin proteins to a successful infection. This has been shown with myxoma virus where in vivo studies showed increased viral attenuation with knockout of ANK repeat protein M-T5 in comparison to knockouts of the ANK/F-box proteins M148R, M149R, and M150R, [ 84 , 95 , 101 ] reflecting a more potent role for M-T5 in enabling a virulent and systemic infection. A prominent role in virulence and host-range for the ANK repeat proteins is also shown by the characterisation of attenuated strains generated by extensive cell-passage, which frequently and apparently preferentially, result in deletion or mutation of ANK repeat proteins, as shown with attenuated strains of myxoma virus, sheeppox virus, fowlpox virus, and orf virus [ 33 , 101 , 102 , 103 ].…”
Section: Poxviral Ank/f-box Protein Phylogeneticsmentioning
confidence: 84%
“… Interactions of ANK/F-box proteins are known from several poxviral species of the Avipoxviru s (AVPV) [ 117 , 122 ], Parapoxvirus (PPOV) [ 78 ], Orthopoxvirus (OPXV) genera [ 79 , 80 , 81 , 82 , 83 , 106 , 109 , 115 , 116 ], and also the Leporipoxvirus super-group (LSG) genera [ 84 , 101 , 123 ]. These poxviral proteins bind to Skp1 via F-box domains, and in some cases also interact with other cellular proteins or have an effect on other cellular systems, most frequently the canonical activation of NF-κB1 transcriptional regulation.…”
Section: Role Of Poxviral Ankyrin Proteinsmentioning
confidence: 99%
“…Inoculation of sheep with this variant produced lesions that were reduced in size and resolved more quickly than wild-type lesions, but it was not possible to determine if ov008 contributed to these differences. Future studies may need to consider the deletion of multiple combinations of the 5 ORFV ANK protein-encoding genes (49).…”
Section: Discussionmentioning
confidence: 99%
“…Six-week-old female New Zealand White rabbits (weight, 1.8 to 2.0 kg; Charles River Laboratories) were inoculated intradermally with 1,000 focus-forming units (FFU) of MYXV in 100 l sterile phosphate-buffered saline (PBS). The rabbits were then monitored for the course and severity of disease as previously described (27). In short, the animals were scored daily for each of 14 variables: posture, eating and drinking, attitude, hydration, eyes, ears, nose, respiration, heart rate, temperature, weight, feces, primary lesion, and secondary lesions.…”
Section: Methodsmentioning
confidence: 99%
“…New Zealand White rabbits were injected intradermally with 1 ϫ 10 3 FFU of either vGFP (n ϭ 3), vM083 (n ϭ 3), or vM083 invert (n ϭ 3). The course of disease was then monitored daily, as previously described (27) (Fig. 4A).…”
Section: Creation Of Myxv Lacking M083lmentioning
confidence: 99%